2013
DOI: 10.1017/s1431927613013706
|View full text |Cite
|
Sign up to set email alerts
|

A Simple and Efficient Method to Observe Internal Structures of Helminths by Scanning Electron Microscopy

Abstract: Morphological studies of helminths by scanning electron microscopy are generally limited to the external topography of the organisms. In this work, we present a simple technique using ethanol as a cryoprotectant without postfixation in osmium tetroxide that allows for observation of the inner organization of helminths and preserves cellular structures. We tested the technique in three helminths: Echinostoma paraensei, Cruzia tentaculata, and Hassalstrongylus epsilon. The results show that this technique could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…Over the last decade, the cryofracture technique has been proved a simple method used to prepare biological samples by exposing internal structures for visualization using SEM (Taylor, 2008). Indeed, previous studies have provided valuable new information about parasitic flukes (Adnet et al ., 2013). As mentioned above, in order to better characterize the uterine eggs observed by CM, a detailed examination using the cryofracture technique was performed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the last decade, the cryofracture technique has been proved a simple method used to prepare biological samples by exposing internal structures for visualization using SEM (Taylor, 2008). Indeed, previous studies have provided valuable new information about parasitic flukes (Adnet et al ., 2013). As mentioned above, in order to better characterize the uterine eggs observed by CM, a detailed examination using the cryofracture technique was performed.…”
Section: Discussionmentioning
confidence: 99%
“…Ten specimens were processed for SEM based on a previous protocol (Lopes-Torres et al ., 2013) and some specimens were frozen and fractured following a simple methodology previously described (Adnet et al ., 2013). Briefly, samples were dehydrated in a graded ethanol series (70–100% Degree Gay Lussac) for 40 minutes at each step, critical-point dried in CO 2 , mounted on metallic stubs and coated with gold (20–25 nm deposited).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional samples of barbs of the same feather and further sectioning of the same material above were observed in Scanning Electron Microscopy (SEM) and in Transmission Electron Microscopy (TEM) to verify some of the findings using STEM. TEM (Jeol 1200 EX, at HV = 80 kV) images were used to understand the internal characteristics of regular melanosomes and their overall shape, which were then corroborated by cryofractured barbs (preparation following Adnet et al, 2013) observed in a SEM microscope (Phillips XL 30, at HV = 12 kV and WD = 8 mm) (Supplementary Material online). The surface features found in the STEM images (see below), were verified on further sections observed in a SEM Zeiss Auriga (FIB-SEM) at HV = 0.5-3.0 kV and WD = 4-8 mm (Supplementary Material online).…”
Section: Sample Preparation and Observationmentioning
confidence: 99%